Effect of Sodium on the Structure‐Performance Relationship of Co/SiO2 for Fischer‐Tropsch Synthesis. Issue 6 (8th May 2017) - Dai, Yuanyuan; Yu, Fei; Li, Zhengjia; An, Yunlei; Lin, Tiejun; Yang, Yanzhang; Zhong, Liangshu; Wang, Hui; Sun, Yuhan
Abstract: A series of Co/SiO2 catalysts with different sodium (Na) loadings (0, 0.1, 0.2, 0.5 and 1 wt%) were prepared and evaluated for Fischer‐Tropsch reaction to study the effect of Na on the catalyst structure and catalytic performance. The addition of Na was found to decrease the catalytic activity and hydrocarbon selectivity, but increase CO2 selectivity due to the enhanced WGS activity. The addition of Na also resulted in higher selectivity to oxygenates (alcohols and aldehydes) and O/P ratio as well as the shift of hydrocarbons to lower carbon numbers. Structure characterization revealed a decrease in the surface area and particles size for the calcined samples with the addition of Na. Co2 C was formed during the reaction process for the Na‐promoted catalysts. As a result, a new Co/Co2 C bifunctional active sites were generated for oxygenates formation leading to increasing oxygenates selectivity. In addition, the Co2 C nanoparticles alone may also act as dual active sites for oxygenate formation at high reaction pressure over the promoted catalysts with high Na loading. Abstract : The effect of Na on the structure‐performance relationship of Co/SiO2 for Fischer‐ Tropsch synthesis was studied. The presence of Na promoted the formation of cobalt carbide and resulted in high selectivity to oxygenates and olefins.